Role of education in future prospects after retirement - Dr Preeti Tarkar (International Journal of Modern Agriculture, 2020)
Due to increment in the life expectancy rates worldwide, the need for conducting more studies on old age persons is increasing. The aim of this study is to investigate the role of education in analyzing the prospects after retirement. Data was collected from the government retirees through a structured questionnaire. The sample size for this study was 302 retired professionals. The questionnaire included questions related to the (e.g. gender, education level) and prospects after retirement. Snowball sampling was used. ANOVA was used to analyze the data. On the basis of findings, there is a significant difference between the prospects for work after retirement on education basis. The finding of the study shows that more options for work are available for the persons on the basis of education. One of the main findings of the current study is that education plays a major role in old age for providing more job prospects to the persons.